Biomedical Engineering Health Care Systems, Technology and Techniques - Suh, Sang C.; Gurupur, Varadraj P.; Tanik, Murat M.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
Biomedical Engineering: Health Care Systems, Technology and Techniques is an edited volume with contributions from world experts. It provides readers with unique contributions related to current research and future healthcare systems. Practitioners and researchers focused on computer science, bioinformatics, engineering and medicine will find this book a valuable reference.
Medical Devices Design Based on Environment-Based-Design -- The Great Migration: Information Content to Knowledge Using Cognition Based Frameworks -- Design and Process Development for Smart Phone Medication Dosing Support System and Educational Platform in HIV/AIDS-TB Programs in Zambia -- Image-Based Methodologies and their Integration in a Cyber-Physical System for Minimally Invasive and Robotic Cardiac Surgeries -- Implementing a Transdisciplinary Education and Research Program -- JIGDFS: A Secure Distributed File System for Medical Image Archiving -- Semantic Management of the Submission Process for Medicinal Products Authorization -- Sharing Healthcare Data by Manipulating Ontological Individuals -- Sharing Cancer Related Genes Research Resources on Peer-to-Peer Network -- IHCREAD: An automatic Immunohistochemistry Image Analysis Tool -- A Systematic Gene Expression Explorer Tool for Multiple and Paired Chips -- On Solving Some Heterogeneous Problems of Healthcare Information Sharing and Interoperability Using Ontology Computing -- Clinical Applications and Data Mining -- Image Processing Techniques in Biomedical Engineering -- Probabilistic Techniques in Bioengineering -- A Complete Electrocardiogram (ECG) Methodology for Assessment of Chronic Stress in Unemployment -- Coherence of Gait and Mental Workload -- Efficient Design of LDPC Code for Wireless Sensor Networks -- Toward Multi-Service Electronic Medical Records Structure -- The New Hybrid Method for Classification of Patients by Gene Expression Profiling -- New Musculoskeletal Joint Modeling Paradigms -- The Role of Social Computing for Health Services Support.
Keywords: Computer science; Bioinformatics; Computer engineering; Biomedical engineering; Computer Science; Information Systems Applications (incl. Internet).; Computational Biology/Bioinformatics.; Biomedical Engineering; Mathematical and Computational Biology; Electrical Engineering